2020
DOI: 10.3390/ijms21207518
|View full text |Cite
|
Sign up to set email alerts
|

RNAi-Mediated Knockdown of Transcription Factor E93 in Nymphs of the Desert Locust (Schistocerca gregaria) Inhibits Adult Morphogenesis and Results in Supernumerary Juvenile Stages

Abstract: Postembryonic development of insects is coordinated by juvenile hormone (JH) together with ecdysteroids. Whereas the JH early response gene krüppel-homolog 1 (Kr-h1) plays a crucial role in the maintenance of juvenile characteristics during consecutive larval stages, the ecdysteroid-inducible early gene E93 appears to be a key factor promoting metamorphosis and adult morphogenesis. Here, we report on the developmental and molecular consequences of an RNAi-mediated knockdown of SgE93 in the desert locust, Schis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 58 publications
1
10
0
Order By: Relevance
“…Our results showed that downregulation of LmE93 generate supernumerary nymphal instars. Similar phenotypes (supernumerary nymphal instar or second pupa) were found after E93 knockdown in other insects including D. melanogaster , T. castaneum , B. germanica , G. bimaculatus , C. lectularius , B. mori , S. gregaria and N. lugens (Ureña et al ., 2014; Liu et al ., 2015; Gujar & Palli, 2016; Li et al ., 2018; Ishimaru et al ., 2019; Gijbels et al ., 2020), suggesting that the function of E93 is conserved among insects. In our study, we also found that ds LmE93 ‐treated individuals remained in N4 and N5 nymphal stages for significantly shorter days.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results showed that downregulation of LmE93 generate supernumerary nymphal instars. Similar phenotypes (supernumerary nymphal instar or second pupa) were found after E93 knockdown in other insects including D. melanogaster , T. castaneum , B. germanica , G. bimaculatus , C. lectularius , B. mori , S. gregaria and N. lugens (Ureña et al ., 2014; Liu et al ., 2015; Gujar & Palli, 2016; Li et al ., 2018; Ishimaru et al ., 2019; Gijbels et al ., 2020), suggesting that the function of E93 is conserved among insects. In our study, we also found that ds LmE93 ‐treated individuals remained in N4 and N5 nymphal stages for significantly shorter days.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, it was found that E93 is highly expressed in the pupal stage and E93‐depleted larvae result in a failure in pupal–adult transition (Mou et al ., 2012; Ureña et al ., 2014, 2016). Several years later, functional studies confirmed E93 as a universal “adult specifier gene”, because knockdown of E93 induced reiteration of larval development to prevent pupal–adult or nymphal–adult and resulted in a supernumerary pupa or nymphal stage (Ureña et al ., 2014; Liu et al ., 2015; Gujar & Palli, 2016; Li et al ., 2018; Ishimaru et al ., 2019; Kamsoi & Belles, 2020; Gijbels et al ., 2020). Moreover, E93 has shown to be related to the JH signaling pathway.…”
Section: Introductionmentioning
confidence: 99%
“…At the penultimate instar stage in Tribolium castaneum , for instance, depletion of E93 perpetuates its juvenile identity by inducing the repetition of larval moults [ 13 ]. In immatures of the hemimetabolous Blattella germanica , Schistocerca gregaria , Locusta migratoria , Gryllus bimaculatus , Cimex lectularius and Nilaparvata lugens , depletion of E93 disallowed the nymphal-to-adult transformation, causing supernumerary juvenile instars [ 15 , 24 , 25 , 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…The significant reduction in Scg-Krh1 demonstrates that JH signaling was impaired upon knocking down Scg -Met ( Figure 2 A). E93 is an ecdysone inducible transcription factor, of which the expression is inhibited by Kr-h1, and vice versa [ 23 , 69 , 70 , 71 , 72 ]. In line with this, an increase in the relative mRNA levels of Scg -E93 was observed in the CA ( Figure 2 A).…”
Section: Discussionmentioning
confidence: 99%